Cephalometric Norms of Bangladeshi Young Children Based on McNamara's Analysis - Khanum Huzzatun Nahar Khawla Binta Harun; Mohammad Tofazzal Hossan; Tanjila Akter; Faria Tabassum Tanni; Gazi Shamim Hasssan; Mahmood Sajedeen (Update Dental College, 2022)
Objective: To evaluate the cephalometric norms of Bangladeshi young children using McNamara's analysis. Methods: It was a descriptive cross-sectional study carried out in the Department of Orthodontics, BSMMU among the dental patients visiting Dental OPD of BSMMU. The test sample was 40 Cephalometric radiographs of patients of which 20 were boys (group I) and 20 were girls (group II). The study respondents were of Bangladeshi origin, aged between 11 and 18 years at the time of cephalometric radiograph taken. A randomized sampling technique was followed to collect samples. Results: The mean cephalometric values of McNamara variables were measured and compared with the Caucasian children and Bangladeshi adults. The p values of all variables for Group I (boys) and Group II (girls) were more than 0.05 which was not significant. So it was interpreted that there was no significant difference in the values of McNamara variables between Bangladeshi boys and girls. But in comparison to Caucasian children the p-value of all the variables was significant (<0.05) except Pogonion to Nasion perpendicular. This result suggested that the McNamara variables for Bangladeshi children were significantly different from Caucasian children.  Conclusion: The values observed by this study can be used in Bangladeshi children irrespective of gender because there is no statistically significant gender difference. It was also observed that the maxilla of the Bangladeshi children was slightly protrusive but the mandible was retrusive than the Caucasian children and both upper and lower incisors were found proclined. Update Dent. Coll. j: 2022; 12(1): 22-26